Doing business amidst conflict : two essays on the distribution of basic consumer goods (2017)
"Violence derived from armed conflict poses great challenges for organizations that either operate or distribute their products in areas affected by violence. this dissertation is composed of two essays that explore this problem. The first essay explores the nonprofit incentives that underlie the contractual arrangements that shape the distribution of basic consumer goods, and how these change under the auspices of political violence. As uncertainty rises, freight generators willingly give up control to manage this complex situation and therefore protect its legitimacy and sustainability. Distributors are willing to accept more uncertainty if it allows them to grow their business and gain independence... The second essay studies the way freight generators adjust their distribution contracts to legally navigate unfavorable, violent environments. To respond to violence, organizations alter their distribution contractual arrangements. The central hypothesis of this paper is that as violence rises, so does organizational decentralization." -- Tomado del Formato de Documento de Grado.